Postoperative Wound Complications in Obstetrics and Gynecology. Treatment and prevention methods - Sawicki, Mirosław; Nowak, Wojciech; Gołębski , Maciej; Mikołajczyk, Jagoda; Kukla , Zuzanna; Mieruszyńska, Stella; Krzemińska, Paulina; Sadowska, Izabela; Włosiański, Jakub; Musialik, Sebastian (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Postoperative wound complications are a significant concern in obstetrics and gynecology, particularly with the increasing cesarean section rates globally. This study aims to analyze and evaluate current prevention and treatment methods for postoperative wound complications, focusing on cesarean sections, while identifying innovative approaches and knowledge gaps to inspire further research. Description of the State of Knowledge: The most frequent complications—SSI, wound dehiscence, and fistula formation—are exacerbated in high-risk groups, such as patients with diabetes, obesity, hypertension, or those undergoing emergency cesarean sections. While surgical advancements and new wound care materials offer potential solutions, discrepancies in their efficacy, particularly for high-risk populations, remain unresolved. Techniques such as continuous suturing and mass closure reduce hernia risks, while innovative interventions, including Negative Pressure Wound Therapy and active dressings (hydrogel, hydrocolloid, alginate), show promise in promoting healing and minimizing complications. Materials and Methods: This study involved a comprehensive literature review of databases such as PubMed, Medline, and Cochrane, focusing on surgical techniques, wound healing mechanisms, and advanced dressing technologies. Results: Findings underscore the value of continuous suturing and mass closure techniques in reducing postoperative hernias and other complications. Innovative methods, including NPWT and active dressings, demonstrate potential in improving healing outcomes for high-risk patients. Summary: Optimizing surgical techniques and postoperative wound care protocols is essential for reducing complications. Further research is needed to standardize guidelines and assess innovative wound management strategies, particularly in obstetrics and gynecology.